2005
DOI: 10.1103/physrevlett.95.130602
|View full text |Cite
|
Sign up to set email alerts
|

Equality Connecting Energy Dissipation with a Violation of the Fluctuation-Response Relation

Abstract: In systems driven away from equilibrium, the velocity correlation function and the linear-response function to a small perturbation force do not satisfy the fluctuation-response relation (FRR) due to the lack of detailed balance in contrast to equilibrium systems. In this Letter, an equality between an extent of the FRR violation and the rate of energy dissipation is proved for Langevin systems under nonequilibrium conditions. This equality enables us to calculate the rate of energy dissipation by quantifying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
378
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(392 citation statements)
references
References 24 publications
13
378
1
Order By: Relevance
“…Formal treatments of fluctuationresponse in periodically forced systems by Teramoto, Harada, and Sasa 74,75 provide insight into the rate of energy dissipation in such systems. Green et al 76 have shown that the rate of energy dissipation is directly related to the dynamical entropy of the system.…”
Section: Characterizing Noisy Reactions With the Noise-free Geometrymentioning
confidence: 99%
“…Formal treatments of fluctuationresponse in periodically forced systems by Teramoto, Harada, and Sasa 74,75 provide insight into the rate of energy dissipation in such systems. Green et al 76 have shown that the rate of energy dissipation is directly related to the dynamical entropy of the system.…”
Section: Characterizing Noisy Reactions With the Noise-free Geometrymentioning
confidence: 99%
“…The expression in Eq. (24) suggests that the it might be related to the violation of the fluctuation dissipation relation in the NESS [26][27][28]. It should be scrutinized further in future.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It has been shown that the special choice of f c = −T ∇ x φ ss guarantees Eq. (26). One may ask whether the converse is also true.…”
Section: Nonconservative Force Casementioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, e.g. [2,8,17] about nonequilibrium linear response, while in the same spirit, the nonequilibrium dynamics was not explicitly time-dependent. We need these new formulae (derived in the Appendix) however for the application described in this paper.…”
Section: Linear Response Around Time-dependent Nonequilibriamentioning
confidence: 99%